Early lexical expression in typically developing Maltese children: implications for the identification of language delay. (July 2013) - Gatt, Daniela; Grech, Helen; Dodd, Barbara
<x xml:space="preserve">Abstract</x> Limited word production may be the first indicator of impaired language development. The unavailability of normative data and standardized assessments for young Maltese children hinders the identification of early language delays. This study aimed to document Maltese children's expressive vocabulary growth and accompanying range of variation, to assist identification of children at risk for language impairment. The expressive vocabularies of 44 typically developing children aged 12–30 months were measured through caregiver report. Mean scores at each age point were characterized by substantial individual variation. Gender was not related to mean growth in vocabulary production. Minimum scores were compared to clinical thresholds for English-speaking children. Results emphasized the assessment- and language-specific nature of identification criteria. Nevertheless, established thresholds may be referred to when normative data for particular languages/language pairs are limited. In such contexts, the consideration of other risk markers gains importance in supplementing findings on lexical expression.